Diseño e implementación de la interfaz hmi mediante labview para el monitoreo de temperatura de masa en los billets de aluminio en la aleación 6063 en la empresa Cedal S.A - Atuña Siza, Segundo Benjamin (2022)
The variables control within the production processes are of utmost importance, since through, these production variables can be assessed the product quantity and quality ensured, the homogenized is a thermal treatment that made at high temperatures into prolonged periods, this in order to eliminate internal stresses, to ensure product quality, it is important, what the billets comply with the heating, it is necessary a monitoring and data acquisition system for the mass temperature curve visualization in the aluminum billets in the homogenizing process. The Enterprise CEDA S.A Latacunga, it does not have this monitoring system, since the aim technological proposal was to create a Man-Machine Interface, from here on it will call it (HMI), which it will allow more than monitoring, mass temperature visualization into aluminum billets for the 6063 alloy in the foundry area. For this research, it was used the inductive method for the materials selection, the programming software, the measuring instrument and the program graphical interface, it was used the scientific method for the temperature in aluminum billets behavior analysis compared with bibliographical sources the homogenate characteristic curve into relation to the got curve by means of the program in LabVIEW. It was achieved to implement the HMI with an easy and user-friendly environment, where data can be collected and stored in an Excel (csv), allowing the user to visualize the mass temperature behavior in real time during 24 hours a day. Through the got data were made a comparison between the air temperature inside the oven and the dough temperature, it was verified with this the homogenizing stage fulfillment.